RNA-Seq transcriptome analysis of porcine cloned and in vitro fertilized blastocysts - Wei-hua XU; Zi-cong LI; Zhi-ping OUYANG; Bo YU; Jun-song SHI; De-wu LIU; Zhen-fang WU (Journal of Integrative Agriculture, 2015)
Somatic nuclear transfer technology has become increasingly promising in biomedicine and agriculture. Whereas the approach remains inefficient and underlying mechanisms remain ambiguous. Although cloned embryos have similar in vitro developmental capacity as in vitro fertilized (IVF) embryos before implantation, they appeared to have much lower full-term developmental efficiency in pig and cattle, and thus it would be reasonable to postulate that profound distinction at the molecular level should exist between them. Herein, RNA sequencing technique was used to screen differentially expressed genes in cloned and IVF blastocysts, and in total 628 differentially expressed transcripts were obtained, among which, 280 transcripts are up-regulated and 348 transcripts are down-regulated in cloned blastocysts. Moreover, one statistically significant pathway associated with endoplasmic reticulum (ER) protein processing was enriched, and some ER-stress markers such as ATF4, ATF6, PDIA3, HSPA1B, HSP40 and HSP90 between cloned and IVF blastocysts were suggested. Additionally, some developmentally important genes such as lipid metabolism related genes (MGLL, DDHD2 and FADS2) and epigenetic modification genes (DNMT1, KDM5C and MBD3L5) were found differentially expressed between cloned and IVF embryos.